Variation in timely surgery for hip fracture by day and time of presentation: a nationwide prospective cohort study from the National Hip Fracture Database for England, Wales and Northern Ireland. Issue 7 (12th August 2020) - Shah, Anjali; Matharu, Gulraj S; Inman, Dominic; Fagan, Elizabeth; Johansen, Antony; Judge, Andrew
Abstract : Background and Objective: Several studies report poorer quality healthcare for patients presenting at weekends. Our objective was to examine how timely surgery for patients with hip fracture varies with day and time of their presentation. Methods: This population-based cohort study used 2017 data from the National Hip Fracture Database, which recorded all patients aged 60 years and over who presented with a hip fracture at a hospital in England, Wales and Northern Ireland. Provision of prompt surgery (surgery within 36 hours of presentation) was examined, using multivariable logistic regression with generalised estimating equations to derive adjusted risk ratios (RRs). Time was categorised into three 8-hour intervals (day: 08:00–15:59, evening: 16:00–23:59 and night: 00:00–07:59) for each day of the week. The model accounted for clustering by hospital and was adjusted by sex, age, fracture type, operation type, American Society of Anesthesiologists grade, preinjury mobility and location. Results: We studied 68 977 patients from 177 hospitals. The average patient presenting during the day on Friday or Saturday was significantly less likely to undergo prompt surgery (Friday during 08:00–15:59, RR=0.93, 95% CI 0.91 to 0.96; Saturday during 08:00–15:59, RR=0.91, 95% CI 0.88 to 0.94) than patients in the comparative category (Thursday, during the day). Patients presenting during the evening (16:00–23:59) were consistently significantly less likely to undergo prompt surgery, and the effect was more marked on Fridays and Saturdays (Friday during 16:00-23:59, RR=0.83, 95% CI 0.80 to 0.85; Saturday during 16:00–23:59, RR=0.81, 95% CI 0.78 to 0.85). Patients presenting overnight (00:00–07:59), except on Saturdays, were significantly more likely to undergo surgery within 36 hours (RR>1.07). Conclusion: The provision of prompt hip fracture surgery was complex, with evidence of both an 'evening' and a 'night' effect. Investigation of weekly variation in hip fracture care is required to help implement strategies to reduce the variation in timely surgery throughout the entire week.